Identifying Child Anxiety Through Schools-identification to intervention (iCATS-i2i): protocol for a cluster randomised controlled trial to compare screening, feedback and intervention for child anxiety problems to usual school practice - Reardon, T; Ukoumunne, OC; Violato, M; Gray, A; Pollard, J; Taylor, L; Williamson, V; Day, E; Fisk, J; Green, I; Halliday, G; Hennigan, C; et al. (BioMed Central, 2022)
Background Systematically screening for child anxiety problems, and offering and delivering a brief, evidence-based intervention for children who are identified as likely to benefit would minimise common barriers that families experience in accessing treatment. We have developed a short parent-report child anxiety screening questionnaire, and procedures for administering screening questionnaires, sharing screening outcomes with families, and offering and delivering a brief parent-led online intervention (OSI: Online Support and Intervention for child anxiety) through schools. This trial aims to evaluate clinical and health economic outcomes for (1) children (aged 8–9) who screen positive for anxiety problems at baseline (target population) and (2) the wider population of all children in participating classes (total population) in schools randomly allocated to receive identification-to-intervention procedures and usual school practice (‘screening and intervention’), compared to assessment and usual school practice only (‘usual school practice’).